Urinary disorders after spinal cord injury and their treatment using botulinum toxin-A endovesical injections - Černiauskienė, Aušra; Genytė, Vaiva; Jukna, Povilas (Lietuvos chirurgija, 2017)
Neurogenic bladder in patients after spinal cord injury is a significant problem. A severe spinal cord injury might produce overactive bladder, detrusor’s hyperactivity which results in urine leaking during storage phase. The loss of supraspinal control that normally coordinates detrusor contraction and sphincter relaxation during urination, can lead to segmental spinal cord reflex-mediated simultaneous contractions of detrusor and sphincter or on the contrary to detrusor-sphincter dyssynergia, resulting in inefficient urine voiding and high residual volume. These disease-related alterations may deteriorate patient’s quality of life, therefore different approaches are being applied for patient’s well-being. Anticholinergic medications are currently first choice for treatment of neurogenic detrusor over-activity. If anticholinergic drugs are not effective and surgery is not an option, injections of botulinum toxin-A to detrusor or urethral sphincter can be chosen for lowering bladder pressure and decreasing the number of urinary incontinence episodes. Botulinum toxin-A injections is a new highly efficient method with rare side effects, therefore this procedure is becoming a promising future in bladder dysfunction treatment. The botulinum toxin-A treatment can be performed repeatedly.
Keywords: spinal cord injury; urinary disorders; botulinum toxin